Mineralogical characteristics of graphite ore from Bao Ha deposit, Lao Cai Province and proposing a wise use - Thao, Hoang Minh; Hien, Tran Thi; Anh, Dao Duy; Nga, Pham Thi (Vietnam Journal of Earth Sciences, 2017)
Graphite, especially, high quality graphite can be used in many industrial applications including metallurgy, batteries, fuel cells, and refractories. In 2011, Vietnam Ministry of Natural Resources and Environment issued a mineral exploration license to explore Bao Ha graphite deposit, Bao Yen district, Lao Cai Province. The studied samples were taken from 3 drill holes of the Bao Ha largest ore body. Different methods including light microscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), and carbon and sulfur analyzer were performed to identify its lithological and mineralogical characteristics as well as graphite quality, then propose a wise use of the resource. The Bao Ha graphite is characterized as disseminated flake graphite in massive form, which developed in the sillimanite schist and quartz-biotite schist of the Ngoi Chi formation. Graphite flakes occur as distorted clusters of flaky plates/flakes within 50÷500 mm, which is the medium size in comparison with the general grain size of graphite flake. Graphite particle makes up 33÷43% by volume and graphitic content (Cg) makes up 10.0÷11.7 wt.%. Impurities include mainly quartz, biotite, and feldspar (combining of K-feldspar and anorthite, the primary ore) or kaolinite (the weathered ore). This graphite ore should be refined to reach an ore concentration of at least 90% Cg for domestic industries of metallurgy, batteries, thermal materials, and refractories as well as for exports.ReferencesAsbury Carbons, 2015. Natural graphite - Introduction to natural graphite. http://asbury.com/technical-presentations-papers/materials-in-depth/natural-graphite/(Accessed on April 26, 2015). Bergmann J., Friedel P., Kleeberg R., 1998. BGMN - a new fundamental parameters based Rietveld program for laboratory X-ray sources, its use in quantitative analysis and structure investigations. CPD Newsletter 20, 5-8. Bien Xuan Thanh (Editor), 2014. Exploration of graphite deposit in Bao Ha area, Bao Ha community, Bao Yen district, Lao Cai province. Report. Song Da Lao Cai Mining Joint Stock Company. Cameron E., 1960. Graphite: Industrial Minerals and Rocks. Seeley W. Mudd Series, AIME (Chapter 20). European Commission, 2010. Report lists 14 critical mineral raw materials. http://europa.eu/rapid/press-release_MEMO-10-263_en.htm?locale=en. (Accessed on April 26, 2015). Garnier V., Giuliani G., Ohnenstetter D., Fallick A.E., Dubessy J., Banks D., Vinh H.Q., Lhomme T., Maluski H., Pêcher A., Bakhsh K.A., Long P.V., Trinh, P.T., Schwarz D., 2008. Marble-hosted ruby deposits from Central and Southeast Asia: Towards a new genetic model. Ore Geology Reviews, 34, 169-191. Hoang Thai Son (Editor), 1997. Geological and Mineral Resources Map of Vietnam at 1:50,000 scale, sheets Doan Hung - Yen Binh. General Department of Geology and Minerals of Vietnam. Hoang Thai Son, Pham Ngoc Thach, Nguyen The Trung, Chu Hong Phong, Nguyen Ngoc Dung, Pham Xuan Doanh, 2000. Disscussion about metamorphism facies of Song Hong Series. Proceedings. General Department of Geology and Minerals of Vietnam. Industrial Minerals, 2011. Supply Situation Report: Graphite demand soars above precrisis levels. http://www.indmin.com/Print.aspx?ArticleId=2797590 (Accessed on April 04, 2011). Industrial Minerals, 2012. The Natural Graphite Report 2012-Data, analysis and forecast for the next five years. http://www.indmin.com/downloads/reports/graphite2012.pdf. Kleeberg R., Ufer K., Bergmann, 2005. The Quantification of Disordered Clay Minerals by the Rietveld Method - Some Practical Aspects. Presentation at the 42nd Annual Meeting of the Clay Minerals Society, June 11-15, 2005, Burlington/Vermont. Lu X. and Forssberg E., 2001. Flotation selectivity and upgrading of Woxna fine graphite concentrate. Mineral Engineering, 14(l l), 1541-1543. Lu X. and Forssberg E., 2002. Preparation of high-purity and low-sulphur graphite from Woxna fine graphite concentrate by alkali roasting. Minerals Engineering. 15(10), 755-757. Luu Huu Hung (Editor), 2001. Evaluation on graphite of Bao Ha area, Bao Yen, Lao Cai. Report. General Department of Geology and Minerals of Vietnam. Ministry of Industry and Trade, 2016. Circular - amending and supplementing a number of articles of the Minister of Industry and Trade’s circular no. 41/2012/TT-BCT of December 21, 2012, providing the export of minerals (July 05, 2016). https://thuvienphapluat.vn/van-ban/Xuat-nhap-khau/Thong-tu-12-2016-TT-BCT-sua-doi-41-2012-TT-BCT-xuat-khau-khoang-san-316914.aspx Mitchell C.J., 1993. Industrial Minerals Laboratory Manual - Flake Graphite. Technical Report. British Geological Survey. Nguyen Vinh, Phan Truong Thi, 1973. Distribution of contact and dynamic metamorphic rocks in Yen Bai - Nghia Lo area. Journal of Sciences and Techniques of Mining and Geology (ISSN: 1859-1469), 22, 1-13. Hanoi University of Mining and Geology. Northern Graphite Corporation, 2015. Bissett Creek Project. <http://northerngraphite.com/bissett-creek-project/> Accessed on April 30, 2015. Persistence Market Research, 2015. Global market study on graphite: Battery segment to witness highest growth by 2020. http://www.persistencemarketresearch.com/market-research/graphite-market.asp. Pham Van Long, Hoang Quang Vinh, Garnier V., Giuliani G., Ohnenstetter D., Lhomme T., Schwarz D., Fallick A., Dubessy J., Phan Trong Trinh, 2004. Gem corundum deposits in Vietnam. Journal of Gemmology, 29(3), 129-147. Pierson H.O., 1993. Handbook of carbon, graphite, diamond and fullerenes - Properties, Processing and Applications. Noyes Publications. Plumbago Co., 2013. What is graphite. http://www.plumbagographite.com/graphite-story/what-is-graphite. (Accessed on April 26, 2015). Rodas M., Luque F.J., Barrenechea J.F., Fernández-Caliani J.C., Miras A., Fernández Rodríguez C., 2000. Graphite occurrences in the Low-Pressure/High-Temperature metamorphic belt of the Sierra de Aracena (Southern Iberian Massif). Mineralogical Magazine, 64, 801-814. Simandl G.J., Paradis S., Valiquette G., Jacob H.L., 1995. Crystalline graphite deposits, classification and economic potential. Proceedings of 28th Forum on the Geology of Industrial Minerals, Marinsburg, West Virginia, May 3-8, 1992, 168-174. Simandl G.J., Paradis S., Akam C., 2015. Graphite deposit types, their origin, and economic significance. In: Simandl G.J. and Neetz M., (Eds.), Symposium on Strategic and Critical Materials Proceedings, November 13-14, 2015, Victoria, British Columbia, British Columbia Ministry of Energy and Mines, British Columbia Geological Survey Paper 2015-3, 163-171. Tran Thi Hien, Vu Tan Co, Chu Van Hoan, Vu Van Ha, Bui Van Ngu, Nguyen Duc Minh, Nguyen Bao Linh, Tran Duc Dung, 2008. Study about mineral processing technology for graphite ore from Nam Thi mine - Lao Cai province. Report. National Institute of Mining - Metallurgy Science and Technology, Vietnam. Tran Van Tri, Vu Khuc (Editors), 2001. Geology and Earth Resources of Vietnam. General Department of Geology and Minerals of Vietnam. Publishing House for Science and Technology, 645p. Tran Xuyen (Editor), 1988. Geological and Mineral Resources Map of Vietnam at 1:200,000 scale, sheets Bac Quang - Ma Quan. Map explanation. General Department of Geology and Minerals of Vietnam. U.S Geological Survey, 2007. 2007 Minerals Yearbook - Graphite. U.S Geological Survey, 10. U.S Geological Survey, 2012. Mineral commodity summaries 2012. U.S Geological Survey, 68-69. U.S Geological Survey, 2017. Mineral commodity summaries 2017. U.S Geological Survey, 74-75. Ufer K., Stanjek H., Roth G., Dohrmann R., Kleeberg R., Kaufhold S., 2008. Quantitative phase analysis of bentonites by the Rietveld method. Clay Mineral 56(2), 272-282. http://dx.doi.org/10.1346/CCMN.2008.0560210. Volkova S.A., Il’icheva O.M., Kuznetsov O.B., 2011. X-ray study of the graphite-bearing rocks from the Pestpaksha ore occurrence and structural features of graphite. Lithology and Mineral Resources, 46(4), 363-368. Vietnam Standards and Quality Institute, 1989. TCVN 4688:1989 Graphite concentrate - Marks and technical requirements.